Estimation of the expected change in domestic human salmonella cases in Sweden in 2010, given a hypothetical relaxation of the current salmonella control programme. - Helene Wahlström; Susanna Sternberg Lewerin; Kristian Sundström; Sofie Ivarsson (PLoS ONE)
The Swedish salmonella control programme has been very successful in reducing the number of salmonella infections in both humans and animals. However, the costs for the control have increased and it has thus been questioned if the control measures could be relaxed and, if so, what effect this would have on human and animal health. The aim of the present study is to evaluate the expected effects on human health of a relaxation of the Swedish control i.e. a substitution of the present programme with a programme similar to the ones present in Denmark or The Netherlands. Data from the year 2010 was used to illustrate this. It was assumed that the domestic exposure to salmonella would then become the same in Sweden as it was in Denmark or the Netherlands in that year. As official statistics on the number of reported salmonella cases are not comparable across European countries, data from five different sources were used to try to obtain comparable estimates of the domestic salmonella exposure in the three countries. The study shows that the number of reported domestic human salmonella cases in Sweden in 2010 would increase by approximately 900 to 2400 cases in the Danish scenarios and 6400 to 8400 in the Dutch scenarios. Although uncertainty exists, it was concluded that the number of reported domestic salmonella cases would increase substantially in Sweden in case of a relaxation of the current control programme.